G-Quadruplexes as tools for synthetic biology - Agarwala, Prachi; Pandey, Satyaprakash; Maiti, Souvik (Chembiochem, 2013)
With the potential to engineer biological systems, synthetic biology is an emerging field that combines various disciplines of sciences. It encompasses combinations of DNA, RNA and protein modules for constructing desired systems and the rewiring of existing signalling networks. Despite recent advances, this field still lags behind in the artificial reconstruction of cellular processes, and thus demands new modules and switches to create genetic circuits. The widely characterised noncanonical nucleic acid secondary structures, G-quadruplexes are promising candidates to be used as biological modules in synthetic biology. Structural plasticity and functional versatility are significant G-quadruplex traits for its integration into a biological system and for diverse applications in synthetic circuits.
Keywords: G-quadruplexes; ribozymes; synthetic biology; topology; zipcodes

Replacement of loop residues in TBA by an abasic ethylene glycol spacer: effect on stability, structure and function** - Wagh, Atish A.; Ghalawat, Monika; Fernandes, Moneesha (ChemistrySelect, 2021)
This article describes the synthesis of ethyleneglycol (E) phosphoramidite and its incorporation into the thrombin binding aptamer (TBA) sequence at loop positions. Circular dichroism (CD) study revealed no major disturbances in the secondary structure of TBA by the abasic E unit and the derived oligomers exhibited a typical antiparallel chair-like conformation similar to that of TBA. UV and CD spectroscopy, together with anti-coagulation and HPLC studies revealed that although nuclease stability was enhanced, and anti-coagulation reasonably good, the thermal stability of the quadruplexes was adversely affected.
Keywords: aptamers; clotting time; ethylene glycol spacer; G-quadruplexes; nuclease stability